POTENTIAL FOR ESTABLISHING FAST GROWING TREE PLANTATIONS IN KOSOVO - Nehat Çollaku; Alketa Grepka; Elvin Toromani (Proceedings on Engineering Sciences, 2025)
Kosovo's forestry sector possesses substantial potential for sustainable forest product production and can significantly contribute to rural economic development. Leveraging this potential could enhance economic growth, create employment opportunities, generate additional income, and aid in poverty reduction. According to the latest report by the Kosovo Agency of Statistics (KAS) on consumption poverty, approximately 18% of Kosovo’s population lives in poverty, struggling to meet basic human needs, while 5.1% live in extreme poverty, unable to meet even the most fundamental survival needs. Sustainable forest management can facilitate carbon sequestration, support biodiversity, and provide renewable energy sources. Currently, wood biomass (primarily as firewood) constitutes Kosovo’s predominant heating source, with an annual consumption of approximately 2.05 million cubic meters. This study investigates the potential for establishing fast-growing tree plantations (FGTPs) and identifies the most suitable sites for their development. A SWOT analysis was conducted to assess the current situation and develop effective policies for the advancement of the wood biomass sector. Economic profitability of FGTPs was assessed using Cost-Benefit Analysis (CBA) and Net Present Value (NPV) methods. Several recommendations are provided for the development of FGTPs in Kosovo, aiming to address national energy demands effectively.